PELABELAN TOTAL TITIK AJAIB PADA COMPLETE GRAPH DENGAN n GANJIL - Irawati, Novi; Soelistyo, Robertus Heri (MATEMATIKA, 2010)
Let G be a graph consists of edges and vertex. A vertex-magic total labeling of a graph  is a bijection map of union edges and vertex to the integers such that there exists a positive integer  satisfying , for every elements of vertex. Then k  is called a magic constant and G is called vertex-magic total graph. In this article, we consider a vertex-magic labeling of complete graph  for odd with use an algorithm which is composed of a modified construction magic square algorithm.